(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Theatrical art occupies an important place in the cultural life of every nation. It is formed as a reflection of the customs, traditions, national values, and social life of the people. Looking at the history of Uzbek theatrical art, one can see that the socio-political processes of the Russian Empire played an important role in its formation. In particular, the national theatrical movement, which emerged in the late 19th and early 20th centuries, began to take shape through the efforts of local intellectuals, Jadids, and art lovers.